Inégalités écologiques, inégalités sociales et territoires littoraux L’exemple du quartier du Chemin Vert à Boulogne-sur-Mer (Pas-de-Calais, France) - Philippe Deboudt; Valérie Deldrève; Vincent Houillon; Didier Paris (Espace populations sociétés, 2008)
A team of sociologists and geographers conducted a research about relations between social and ecological inequalities. The case study is located in a problem urban area, located in Boulogne-sur-Mer (North of France). Basing their analysis on a case study of the Chemin Vert district in Boulogne-sur-Mer, the authors examine the relationship between the socio-urban dimension and the environmental dimension in the construction of social and ecological inequalities. From an integrated geographical and sociological perspective, the authors analyze the construction of urban space and the processes of marginalization that, in the 1990s, were associated to this space, resulting in the concept of zone urbaine sensible (sensitive urban zone). While the authors agree that the social characteristics of the Chemin Vert district place it unequivocally in the category of extremely under-privileged, the district’s environmental inequality is nonetheless limited in comparison to other districts in the city. In fact, although the urban environment of the Chemin Vert is certainly diminished by the lack of access to services, by the mediocre quality of housing, and by the district’s spatial marginalization, it benefits from a "natural" environment that is objectively positive, due to its coastal location and its proximity to the sea. The urban renewal policies financed by France’s National Urban Renovation Agency in 2004 signaled a change in the evolution of this district, notably with an urban project that takes the Chemin Vert’s coastal and maritime dimension into account. A sociological study conducted in 2006-2007 high- lighted the difficulties that the inhabitants have in appropriating the transformations engendered by this urban project. The environment lived in and perceived by the inhabitants differs fundamentally from the one perceived by the territorial stakeholders. The contrasting perspectives of the geographical and sociological approaches act to expand the notion of ecological inequality.